Starting from the child : teaching and learning in the foundation stage - Fisher, Julie (b)
The fourth edition is essentially still about putting the principles of early childhood education into practice.
Includes bibliographical references and index.
Keywords: Early childhood education -- Great Britain; Learning, Psychology of